2022
DOI: 10.3389/fpls.2022.1001208
|View full text |Cite
|
Sign up to set email alerts
|

The effects of allelochemicals from root exudates of Flaveria bidentis on two Bacillus species

Abstract: To determine the allelopathic effects of root exudates from Flaveria bidentis on function of Bacillus, pot experiment was used to collect root exudates from living plants and test its allelopathic effects on function of Bacillus frigoritolerans and Bacillus megaterium, which were two dominant bacteria in the rhizosphere soil of F. bidentis. To obtain the allelopathic substances, the root exudates were successively extracted by N-hexane, dichloromethane, ethyl acetate, and N-butanol, and their allelopathic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Our study also revealed that inoculation with B. cereus weakened the positive effect of interspecific competition on A. adenophora and alleviated the negative effect on R. amethystoides growth but did not change the competitive relationship between A. adenophora and R. amethhystoides (Figure 2). We also found that B. cereus inoculation led to significantly greater promotion on R. amethystoides biomass than A. adenophora, which may be due to the different effect of root exudates from the two plants on the growth-promoting effect of Bacillus (Sun et al, 2021(Sun et al, , 2022. To understand the potential mechanisms, future studies may conduct a comparative analysis of the secondary metabolites of A. adenophora and R. amethystoides and their effect on Bacillus's ability to solubilize phosphorus and fix nitrogen.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our study also revealed that inoculation with B. cereus weakened the positive effect of interspecific competition on A. adenophora and alleviated the negative effect on R. amethystoides growth but did not change the competitive relationship between A. adenophora and R. amethhystoides (Figure 2). We also found that B. cereus inoculation led to significantly greater promotion on R. amethystoides biomass than A. adenophora, which may be due to the different effect of root exudates from the two plants on the growth-promoting effect of Bacillus (Sun et al, 2021(Sun et al, , 2022. To understand the potential mechanisms, future studies may conduct a comparative analysis of the secondary metabolites of A. adenophora and R. amethystoides and their effect on Bacillus's ability to solubilize phosphorus and fix nitrogen.…”
Section: Discussionmentioning
confidence: 80%
“…After shaking at 180 rpm for 24 h at 37°C, the liquid was transferred into a triangular flask containing 100 mL of nutrient liquid broth medium and shaken at 180 rpm for 24 h at 37°C. The Bacillus suspension was then expanded to a concentration of 10 8 CFU/ mL (Sun et al, 2022).…”
Section: Microbial Inoculation Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the phenotypic plasticity, compensatory or tolerance of invasive species, the negative feedback effect is significantly weakened ( Policelli et al., 2018 ). On the other hand, some rhizosphere-beneficial bacteria have a preferential impact on invasive species ( Sun et al., 2022 ). For instance, mycorrhizal fungi significantly improve the disease resistance of host plants, and the invasive plant Anthemis cotula is protected from the invasion of pests and diseases due to the high infection of arbuscular mycorrhizal fungi ( Shah et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA concentration was measured using NanoPhotometer N60 spectrophotometer (IMPLEN, Germany), and the PCR primers for qRT-PCR analysis (Bio-Rad CFX96 touch, Bio-Rad Laboratories Incorporated, USA) were designed based on the sequence of B. cereus strains. The specific determination method referred to the existing research ( Sun et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%